A critique of “resource-based” theories of colombia’s civil war (2008)
In recent years, several Colombian scholars have studied this country’s civil conflict through the lenses of economic reasoning and state-of-the-art statistical testing. Their analyses place most of the explanatory burden of the conflict on the existence of lootable resources and organized crime, not on any specific socio-economic factor of Colombia’s reality (“objective causes”). This paper criticizes their claims while accepting their criteria and methods. In particular, it contends that their formal approach to civil conflicts is flawed, a flaw that carries over to the type of empirical tests conducted and that there are several gaps in the reasoning from statistical results to the overall interpretation of the conflict.